Incidence and Prevalence of Drug-Resistant Epilepsy: A Systematic Review and Meta-analysis. (27th April 2021) - Sultana, Bushra; Panzini, Marie-Andrée; Veilleux Carpentier, Ariane; Comtois, Jacynthe; Rioux, Bastien; Gore, Geneviève; Bauer, Prisca R.; Kwon, Churl-Su; Jetté, Nathalie; Josephson, Colin B.; Keezer, Mark R.
Abstract : Objective: To evaluate the incidence and prevalence of drug-resistant epilepsy (DRE) as well as its predictors and correlates, we conducted a systematic review and meta-analysis of observational studies. Methods: Our protocol was registered with PROSPERO, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and Meta-analysis of Observational Studies in Epidemiology reporting standards were followed. We searched MEDLINE, Embase, and Web of Science. We used a double arcsine transformation and random-effects models to perform our meta-analyses. We performed random-effects meta-regressions using study-level data. Results: Our search strategy identified 10, 794 abstracts. Of these, 103 articles met our eligibility criteria. There was high interstudy heterogeneity and risk of bias. The cumulative incidence of DRE was 25.0% (95% confidence interval [CI]: 16.8–34.3) in child studies but 14.6% (95% CI: 8.8–21.6) in adult/mixed age studies. The prevalence of DRE was 13.7% (95% CI: 9.2–19.0) in population/community-based populations but 36.3% (95% CI: 30.4–42.4) in clinic-based cohorts. Meta-regression confirmed that the prevalence of DRE was higher in clinic-based populations and in focal epilepsy. Multiple predictors and correlates of DRE were identified. The most reported of these were having a neurologic deficit, an abnormal EEG, and symptomatic epilepsy. The most reported genetic predictors of DRE were polymorphisms of the ABCB1 gene. Conclusions: Our observations provide a basis for estimating the incidence and prevalence of DRE, which vary between populations. We identified numerous putative DRE predictors and correlates. These findings are important to plan epilepsy services, including epilepsy surgery, a crucial treatment option for people with disabling seizures and DRE.